HUBUNGAN ASUPAN LEMAK DENGAN STATUS GIZI ANAK USIA 6 BULAN-12 TAHUN DI INDONESIA - Fitrah Ernawati; Pusparini Pusparini; Aya Yuriestia Arifin; Mutiara Prihatini (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2019)
ABSTRACT Indonesia still faces a double burden of malnutrition where malnutrition problems still exist, and the prevalence of obesity continues to increase. The study was intended to evaluate the association between fat intake adequacy and nutritional status in children aged 6 months to 12 years with a middle to upper socioeconomic level. The study design was cross-sectional study using secondary data from the Basic Health Research in 2013 and Indonesian Food Consumption Survey in 2014. The results of the study concluded that more than 50 percent of children aged 6 months to 9 years and 38 percent of children aged 10-12 years old consumed fat more than 100 percent of Recommended Dietary Allowances (RDA). The study revealed a signidficant association between fat intake and body mass index for age Z-score (BAZ) (p <0.05) and fat intake with height for age Z-score (HAZ) (p <0.05). Fat intake of children live in urban was higher than at rural areas (p <0.05) and fat intake of boys was slightly higher than girls. The results of this study suggest the importance of providing nutrition education started from elementary school students on balanced nutrient intake and reduce fat intake, because obesity in early age contribute to obesity in adulthood. Keywords: children aged 6 month to12 years old, fat intake, nutritional status ABSTRAK Indonesia menghadapi masalah gizi ganda yaitu masalah gizi kurang masih ada, dan persentase masalah kegemukan terus meningkat. Tujuan dari analisis ini untuk melihat kecukupan asupan lemak anak usia 6 bulan sampai 12 tahun dengan tingkat sosial ekonomi menengah keatas dan hubungannya dengan status gizi. Desain penelitian adalah potong lintang, jenis data yang digunakan data sekunder dari Riskesdas 2013 dan Survey Konsumsi Makanan Indonesia (SKMI) 2014. Hasil penelitian disimpulkan bahwa lebih dari 50 persen anak usia 6 bulan-9 tahun dan 38 persen anak usia 10-12 tahun mengonsumsi lemak ≥ 100 persen AKG. Terdapat hubungan yang signifikan antara tingkat asupan lemak dengan status gizi menurut indikator IMT/U (p<0,05) dan asupan lemak dengan status gizi TB/U (p<0,05). Asupan lemak anak yang tinggal di kota lebih tinggi dari pada di perdesaan (p<0,05) dan asupan lemak anak laki-laki lebih tinggi dari anak perempuan (p<0,05). Hasil penelitian ini memberikan bukti tentang pentingnya memberikan edukasi kepada siswa sekolah dasar tentang makanan gizi seimbang dan mengurangi asupan lemak, karena kegemukan pada usia dini akan terbawa hingga usia dewasa. [Penel Gizi Makan 2019, 42(1):41-47] Kata kunci: anak usia 6 bulan-12 tahun, asupan lemak, status gizi